NURSE PERFORMANCE INFLUENCES DOCUMENTATION SUCCESS IN IMPLEMENTING DISCHARGE PLANNING IN INPATIENT CARE AT THE HOSPITAL IN BANJARMASIN - Noor Amaliah; Noor Hadijah; Zainal Aripin (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Nurse performance is an activity in implementing authority, duties and responsibilities in order to achieve the main tasks of the profession and organization. Discharge planning is a stage that has the goal of preparing the patient during the post-treatment transition period so that he can return home. Purpose of this study in general was to determine the corre. lation between nurse performance and successful documentation in the implementation of discharge planning at inpatient care at Hospital, Banjarmasin. Method this research is quantitative by using infants and post-partum care, totaling 6,5 executive nurse. in taking the simple Random Sampling Technique. Result. Thus it can be concluded that there is a correlation between the performance variables of nurses and the implementation of discharge planning in the inpatient care of Hospital, Banjarmasin. Health services are expected to always improve the performance of good nurses for health services, especially nurses in implementing discharge planning for patients, nurse performance is very important in completing nursing tasks such as implementing discharge planning in hospitalization. In order to create good quality for the quality of health services in hospitals.